Effect of bleaching protocols on surface roughness and biofilm formation on silorane-based composite resin - Mahmoud Bahari; Mohammad Esmaeel Ebrahimi Chaharom; Mehdi Daneshpooy; Sarah Gholizadeh; Hamed Pashayi (Wolters Kluwer Medknow Publications, 2019)
Background: Knowledge about the effect of bleaching on behavior of composite resins is important to find a suitable composite resin for restoration of teeth undergoing bleaching. This study aimed to assess the effect of different bleaching protocols on surface roughness and biofilm formation on a silorane-based composite resin. Materials and Methods: In this in vitro experimental study, 60 silorane-based composite resin samples measuring 3 mm in thickness and 6 mm in diameter were fabricated and polished. They were then randomly divided into four groups (n = 15). In Group 1, samples were stored in distilled water as control. Samples in Groups 2, 3, and 4 were subjected to bleaching with 15% carbamide peroxide, 35% hydrogen peroxide, and 35% hydrogen peroxide activated by light, respectively. Surface roughness was measured using a profilometer. Streptococcus mutans cultured in brain-heart infusion broth was used for the assessment of biofilm formation on the samples. The bacterial colonies were counted using the pure-plate technique. Data were analyzed using one-way ANOVA and post hoc Tukey's tests. Regression model was used to assess the association between surface roughness and biofilm formation (P < 0.05). Results: The mean surface roughness of the four groups was not significantly different (P = 0.11); however, a significant difference was noted in the mean biofilm formation among the groups (P = 0.00). Conclusion: Bleaching decreased biofilm formation. The lowest biofilm formation was noted in the group subjected to light-activated 35% hydrogen peroxide. Increased surface roughness enhanced biofilm formation to a certain level; excessive roughness did not increase biofilm formation.